Toward climate resilience in the USA. From federal to local level initiatives and practices since the 2000s. - Gencer, Ebru A.; Rhodes, Wesley (Springer, 2018)
Die Arbeit untersucht die Entwicklung des Katastrophenmanagements und die bauliche wie klimapolitische Anpassung an den Klimawandel in den USA in den Jahren 2000-2018 und kommt zu dem Schluss, dass beide Bereiche sich in dieser Zeit am stärksten auf der kommunalen und lokalen Ebene weiterentwickelt haben.

This chapter explores the evolving concept of disaster risk management and climate resilience building in the United States of America (USA) within the last two decades. The chapter starts by examining federal-level actions towards disaster risk management and climate adaptation and resilience and then delves into local-level actions through the case studies of Nashville, Tennessee, and Hoboken, New Jersey. The chapter concludes with a discussion on the future of climate resilience in the USA. The chapter illustrates that the availability of multiple layers of government has been an effective safety guard against any individual layer's potential unwillingness to undertake protective risk management or climate resilience building. At state and regional levels, where political will was lacking, federal-level support, particularly in the Obama era, and the initiatives of private foundations have been very valuable. Nowhere, though, have climate resilience building actions in the USA been proven more effective than at the City administrative level. As everywhere else, local-level governments in the USA are at the forefront of disasters and the impacts of climate change and try to take the initiatives of preparing their cities for protection.
Keywords: Klimawandel; Klimaanpassung; Klimapolitik; Schadensvorbeugung; Bauen (klimagerecht); Krisenmanagement; Kommunaler Klimaschutz; Katastrophenschutzplanung